Safety and efficacy of Everolimus‐Eluting bioabsorbable Polymer‐Coated stent in patients with long coronary lesions: The EVOLVE 48 study. Issue 2 (29th May 2021) - Karmpaliotis, Dimitrios; Stoler, Robert; Walsh, Simon; El‐Jack, Seif; Potluri, Srinivasa; Moses, Jeffrey; Oldroyd, Keith; Banning, Adrian; Webster, Mark; Zaman, Azfar; Wu, Willis; Ahmed, Mudassar; et al.
Abstract: Objectives: The EVOLVE 48 study evaluated the safety and effectiveness of the SYNERGY 48 mm stent for the treatment of long lesions. Background: Clinical evidence supporting the use of very long stents during percutaneous coronary intervention (PCI) is limited. The bioabsorbable polymer SYNERGY stent has shown good long‐term data in a broad population of patients undergoing PCI. Methods: Patients with lesion length >34‐ ≤44 mm and reference vessel diameter (RVD) ≥2.5‐ ≤ 4.0 mm were enrolled in this prospective, multicenter, single‐arm study. The primary endpoint was 12‐month target lesion failure (TLF; composite of target lesion revascularization [TLR], target‐vessel myocardial infarction [TV‐MI], or cardiac death) compared to a prespecified performance goal (PG). Results: A total of 100 patients with mean lesion length of 35.34 ± 7.15 mm (26 patients with lesion length > 40 mm) and mean RVD 2.72 ± 0.44 mm were enrolled. Moderate to severe calcification was present in 30% of the patients and 89% had pre‐TIMI flow grade 3. The rates of technical and clinical procedural success were 100%. One‐year TLF was observed in 4.1% patients compared to a prespecified PG of 19.5% (95% upper confidence bound = 9.1%; p < 0.0001). Cardiac death and TLR were each observed in one patient, and TV‐MI in two patients treated with SYNERGY 48 mm stent. Between the 1‐2‐year timeframe, TV‐MI occurred in one additional patient. None of the patients experienced a definite or probable stent thrombosis through 2 years. Conclusions: PCI of long coronary lesions with the 48 mm SYNERGY stent demonstrated good procedural and clinical outcomes through 2 years, supporting its clinical safety and efficacy.